2021
DOI: 10.1017/s0031182021002031
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination with parasites in selected rural farms in the Philippines: impacts of farming practices on leafy greens food safety

Abstract: Fresh vegetables are an important part of a healthy diet, however, they can also be agents of transmission of intestinal parasites. This study aimed to evaluate the presence of parasite contamination in vegetable farms as a source of transmission in selected rural communities in Laguna, Philippines. A total of 168 vegetable, 55 soil and 15 water samples collected from four selected farms and a reference farm were processed through various standard parasitological techniques. Of these, 17.3% of vegetables, 47.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Discovering Toxocara eggs within the soil used to cultivate vegetables in this study was not entirely unexpected given the presence of these eggs on vegetable crops. This finding is supported by similar studies undertaken in other countries, such as the Philippines ( Paller et al, 2021 ) and Poland ( Klapec and Borecka, 2012 ). Given the small number of soil samples tested in this pilot study, firm comparisons between the prevalence of eggs on vegetable produce and soil cannot be drawn.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Discovering Toxocara eggs within the soil used to cultivate vegetables in this study was not entirely unexpected given the presence of these eggs on vegetable crops. This finding is supported by similar studies undertaken in other countries, such as the Philippines ( Paller et al, 2021 ) and Poland ( Klapec and Borecka, 2012 ). Given the small number of soil samples tested in this pilot study, firm comparisons between the prevalence of eggs on vegetable produce and soil cannot be drawn.…”
Section: Discussionsupporting
confidence: 81%
“…Leafy vegetables such as lettuces have been reported to have higher susceptibility to contamination with Toxocara spp. eggs compared to non-leafy vegetables, possibly due to the folded nature of the leaves, which capture more soil during cultivation ( Hajipour et al, 2021 ; Abougrain et al, 2010 ; Paller et al, 2021 ). This is consistent with the current study, where both positive vegetable samples were from lettuces.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that soil is increasingly recognized as an important source of transmission of T. gondii ( Afonso et al, 2008 ; Escotte-Binet et al, 2019 ) and G. duodenalis ( Balderrama-Carmona et al, 2014 ; Lee et al, 2021 ; Omeragić et al, 2021 ; Paller et al, 2022 ) . However, detecting the presence and estimating the load of T. gondii in soil has been difficult given limitations in the availability of detection methods ( Shapiro et al, 2019a , Shapiro et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Documenting the degree of soil contamination with T. gondii oocysts and G. dudodenalis cysts is fundamental to propose efficacious measures to prevent toxoplasmosis and giardiasis ( Slifko et al, 2000 ; Escotte-Binet et al, 2019 ; Dumètre et al, 2012 ; Lee et al, 2021 ; Paller et al, 2022 ). Molecular assays are currently the most sensitive and effective methods to detect T. gondii and G. dudoenalis in soil ( Orlofsky et al, 2013 ; Shapiro et al, 2019a ; Slifko et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Toxocara spp. eggs were detected on 4.8% of sampled vegetables in a study undertaken in the Philippines, with leafy vegetables found to be most contaminated [5], and in a Brazilian study, 17.8% of sampled lettuces (Lactuca sativa) were found to be positive for Toxocara spp. eggs [6].…”
Section: Introductionmentioning
confidence: 93%